O Programa de Qualidade da Escola da Secretaria de Estado da Educação de São Paulo: o texto e o contexto em três escolas da Diretoria de Ensino - Região de Pirassununga - Castro, Adriana de (2013)
In 2008, the Education Department of São Paulo State (SEE/SP) started the implementation process of the "School Quality Program" and the "Curricular Proposal Project" in all São Paulo State public schools. According to SEE/SP, the purpose of the program is to evaluate each school through annual aims, which are pre-established by SEE/SP and based on two criterias: the school flow and the student s performance in the Evaluation System of São Paulo State (SARES). The aim ends up in an index of Education Development of São Paulo State (IDESP), for each level of education. In this paper, we discuss the School Quality Program from 2008 to 2012, having as parameters the objectives proclaimed by SEE/SP, taking the empirical research data analysed under the theoretical framework composed by Claus Offe and Antonio Gramsci, in relation to the educational improvement quality. The empirical cutting to data collection included eight of the nine poles that made up the Teaching Coordination of São Paulo Contryside and the case study happened in three pre-selected schools, under Pirassununga Teaching Board responsability. We notice the emphasis on the product overlapping the educational process, both for the SEE/SP, through IDESP, and in the surveyed schools organization. Intra and extra factors make up the educational quality for the subject researched and the teacher s evaluation is considered an important quality factor for parents. We see as positive aspects of "School Quality Program", the SEE/SP trying to improve educational quality at public schools and the network-wide deployment of a single curriculum with essential skills and competences for student learning. The Bonus for Results (BR) established with the objective of motivating school teams to achieve the aims of IDESP, is a contradiction. It doesn t motivate teachers, but, provide places and pedagogical time to prepare students for the SATS. The schools surveyed had difficulties to maintain a track record of IDESP improving. Educational quality has a potential converter of social and economical reality, but for that, we have to provide enough public funding for education, enhance the teaching profession and teachers, improve the initial and recurrent training, enable other spaces and times of learning.